Beyond the landscape: Social-behavioral factors as the true coexistence parameters in the Chilean carnivore-livestock conflict - Moreira-Arce, D; Alaniz-Baeza, A (SPRINGER, 2026)
We share land with carnivores throughout the world, but coexistence is not assured. Using a social-ecological systems approach and employing the coexistence parameter concept, we tested whether environmental variables could serve as operational tools to resolve carnivore-livestock conflict in Chile. Our analysis of the national Agricultural and Livestock Service (SAG) database (2011-2019) confirms that Southern Chile is a predation hot spot, with domestic dogs, not pumas, being the primary predator. Environmental variables such as proximity to urban centers and forests explain predation patterns, which are valuable for identifying conflict hot spots and prioritizing interventions. However, we conclude these variables are not realistically manageable mitigation tools. This study strongly suggests that while environmental correlates exist, the true, operational drivers of conflict are social. We conclude that shifting to a state of coexistence in shared landscapes requires a focus on behavioral and societal changes, such as legal and cultural shifts to manage free-roaming dog populations. We offer a research agenda based on key coexistence parameters we have identified to help solve the dog predation of livestock in Chile.